Providing a Model to Determine Span of Control in Financial Organizations - Khadijeh Naboureh; Ehram Safari (مدیریت مهندسی و رایانش نرم)
Span of control is defined as the number of personals who give a report to a manager who manages them directly. A manger with wide span of control may be not able to efficiently control and effectively guide employees. On the contrary, the presence of managers with small span of control is a sign for inefficient organizational structure. Population of Iran and japan is 75 and 110 million, while the number of governmental managers for Iran has become 1.5 times in comparison with the total governmental emploees of Japan. Furthermore, there is a manager for every of the 5 employees in operational and staff departments. Therefore, if the administrative system is not revised, the governmental expenditure will be equal to the total budget and the government must borrow extra resources to maintain its structure. The span of control in financial institutions and banks according to the volume of activities and services offered to them is very important. In this article we have tried to determine the span of control model for financial institutions which improve the effectiveness and efficiency of their organizations.